Sorption and desorption of glyphosate in Mollisols and Ultisols soils of Argentina - Gómez Ortiz, Ana Maria (2017)
In Argentina, glyphosate use has increased exponentially in the past years due to the widespread adoption of no-till management combined with genetically modified glyphosate-resistant crops. This massive use of glyphosate has created concern about its potential environmental impact. Sorption-desorption of glyphosate was studied in three Argentinean soils with contrasting characteristics. Glyphosate sorption isotherms were modeled using the Freundlich equation to estimate the sorption coefficient (Kf). Glyphosate sorption was high and the Kf varied from 115.6 to 1612 mg 1-1/nL1/n /Kg. Cerro Azul soil had the highest glyphosate sorption capacity due to a combination of factors such as higher clay content, CEC, total Fe, Al oxides and lower available phosphorous and pH. Desorption isotherms were also modeled using the Freundlich equation. In general, desorption was very low (<12%). The low values of hysteresis coefficient (H) confirm that glyphosate strongly sorbs to the soils and that it is almost an irreversible process. Anguil soil had a significant higher desorption coefficient (Kfd) than the other soils, associated with its lower clay content and higher pH and phosphorous. Glyphosate high sorption and low desorption to the studied soils may prevent groundwater contamination. However, it may also affect its bioavailability increasing its persistence and favoring its accumulation in environment. Results of this study contribute to the knowledge and characterization of glyphosate retention in different soils.